Linkage between energy supply system and running skill during long distance running race - Yamazaki, K. (Advances in Exercise and Sports Physiology, 2014)
During long distance race running skill changes in progress. Generally this phenomena was concerned with fatigue progress. But in the other perspective this would be a kind of regulation by changing running skill according to reduce of energy supply system. In this study I try to examine hypothesis of Yamazaki`s matrix model of long distance running performance and get biomechanical data of elite long distance runners in actual 10000m race. Subjects were 4 healthy well -trained long distance runners of Niigata University team (representative members of all Japan inter University EKIDEN race). Biomechanical data of four steps were measured at 2000m, 4800m and 8800m by motion analysis soft wear (Silicon Coach). Correlation function value of running speed and stride(S-S), running speed and cadence(S-C) were examined. At 2000m correlation function value of S-S were very high (3/4). At 4800m function value of S-S and S-C were individual. But at 8800m function value of S-C were very high (4/4) and value of S-S were not so high (3/4). These results mean elite runners would change their running skill in race progress. In sprint-running theory speed is decided by upkeep adequate strides and high cadence. Probably good runners would use same strategy to keep their running speed. In this point of view correlation function value of running speed and cadence (S-C) were very high in final stage of 10000m race